Bioinformatic and Functional Analysis of a Key Determinant Underlying the Substrate Selectivity of the Al Transporter, Nrat1 - Lu, Muxue; Yang, Guangzhe; Li, Peifang; Wang, Zhigang; Fu, Shan; Zhang, Xiang; Chen, Xi; Shi, Mingxing; Ming, Zhenhua; Xia, Jixing (Frontiers in Plant Science, 2018)
Nrat1 is a member of the natural resistance-associated macrophage protein (Nramp) family of metal ion transporters in all organisms. Different from other Nramp members capable of transporting divalent metals, Nrat1 specifically transports trivalent aluminum (Al) ion. However, molecular mechanism underlying the Al transport selectivity of Nrat1 remains unknown. Here, we performed structure-function analyses of Nrat1 and other Nramp members to gain insights into the determinants of ion selectivity. A phylogenetic analysis showed that plant Nramp transporters could be divided into five groups. OsNrat1 was found in one of the individual clades and clustered with SbNrat1 and ZmNrat1 on the evolutionary tree. Structural modeling revealed that Nrat1 transporters adopted a common LeuT fold shared by many Nramp-family transporters that likely employed an identical transport mechanism. Sequence alignment and evolutionary conservation analysis of amino acids identified a metal-permeation pathway of Nrat1 centered at the metal binding site. The metal binding site of Nrat1 was characterized by two conserved sequence motifs, i.e., the Asp-Pro-Ser-Asn motif (motif A) and the Ala-Ile-Ile-Thr motif (motif B). Replacement of the Ala-Met-Val-Met motif B of the OsNramp3 manganese (Mn) transporter to that of Nrat1 resulted in a partial gain of Al transport activity and a total loss of Mn in yeast. Conversely, substitution of the motif B of OsNrat1 with that of OsNramp3 altered the Al transport activity. These observations indicated the metal binding site, particularly the motif B, as a key determinant of Al selectivity of Nrat1.